(3QSGdI GHf YWGA Gddgs - (3CMeO Hf eMeO Hf YHO GdcQje CHh GdaVd JGL GdOjf GHf YWGA Gddg GdEScfOQis
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GMdehG QMece Gddg Cf GdYdfGjI GdEdgjI hEf cGfJ ZjHkG adfG TgGOI JOd YdjgG hOdGdGJ JgOi ZdgjG aJdeYhG QMece Gddg YfGjI Gddg ajce jhbhace Ydi MOhOg hQGjJce dYgOg CdG ef YdGeI eMHI Gddg GdYHO eMHJi GdYHO EjGg hef YdGeI eMHIs
(3BNQgG (B:s
(3hbO UM Cf dG EceGd ZdG HGdYde hdG MUf ddYde EdG GdYded adG ebGdI ef UOc Yf hGMO efgeG hdG ef QLM hGMOGU ai eMd BNQ Ohfg hHGddg bd di EPG cGf GdYde hXjaI MJi Jba Hjf Gddg hbaI UOb hMb eJi JUd Edi JMbjb CYeGdc s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3fSNI eWGdYIs
(3HYV CWQGagG eJBcdI s
(3hHChdgG Jedc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B221s
Keywords: (3GdJUha hGdBOGH GdTQYjIs